2014
DOI: 10.4028/www.scientific.net/amm.703.90
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Study on a New Type of Anti-Electromagnetic Radiation Gypsum Board

Abstract: Electromagnetic radiation has become a great threat to human health. In this paper, ferrite and graphite were main absorbing agent, which were prepared to a new type of anti-electromagnetic radiation gypsum board. The results show that the microwave absorbing properties of ferrite/graphite mixed are better than with ferrite or graphite single-agent mixed. The gypsum board with the graphite content of 5wt% and the ferrite content of 25wt% has the best absorbing performance, The effective band width less than-5d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Li et al 19,20 confirmed that chemical vapor deposition treatment upon carbon fibers at 0.2 wt% fraction significantly influenced the concrete's conductivity. Wang et al 21 explored carbon black incorporated hydroxyl iron powder‐epoxy resin as a conductive composite and validated a 95.6% of microwave absorption. However, the GP obtains a relatively smooth texture in microscale, which creates a lubrication effect and negates the micro‐bonding force as well as the macro‐mechanical performance of the ECCC 22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 19,20 confirmed that chemical vapor deposition treatment upon carbon fibers at 0.2 wt% fraction significantly influenced the concrete's conductivity. Wang et al 21 explored carbon black incorporated hydroxyl iron powder‐epoxy resin as a conductive composite and validated a 95.6% of microwave absorption. However, the GP obtains a relatively smooth texture in microscale, which creates a lubrication effect and negates the micro‐bonding force as well as the macro‐mechanical performance of the ECCC 22,23 .…”
Section: Introductionmentioning
confidence: 99%